Novel perspectives on Late Cretaceous elasmobranch diversity in the Southern Hemisphere high latitudes - Begat, Arnaud (2025)
Two new vertebrate assemblages rich in elasmobranch isolated teeth and dermal denticles from the lower Cenomanian (Upper Cretaceous) of Patagonia in southern Argentina comprise ten identified taxa (†Protosqualus sp., †Heterodontus sp., †Orectoloboides sp., †Carcharias sp., †Scapanorhynchus patagonensis sp. nov., †Squalicorax sp., †Paraorthacodus sp., †Rhinobatos aff. †R. incertus, †Ptychotrygon ameghinorum, †Ptychotrygon sp.) and five unidentified lamniforms. The material comes from two closely positioned sites representing proximal palaeoenvironments (delta and lagoonal foot barrier, respectively). The new elasmobranch sites are the most diverse known from the Upper Cretaceous of Patagonia until today and indicate a remarkable elasmobranch diversity in high latitudes of the Southern Hemisphere. They are dominated by warm-water taxa demonstrating a strong Tethyan influence into the southern part of the Austral Basin, contrasting with the later Weddellian influence as indicated by the presence of cold-water taxa in that area during the Campanian and the Maastrichtian.